Degradation of p-chloroaniline using an electrochemical ceramic microfiltration membrane with built-in electrodes. (1st December 2018) - Xu, Shaoping; Zheng, Junjian; Wu, Zhichao; Liu, Mingxian; Wang, Zhiwei
Abstract: An electrochemical ceramic microfiltration membrane with built-in cathode (Ti mesh) and Ti/RuO2 anode, which had dual functions of separation and electrochemical oxidation, was developed for p -chloroaniline (PCA) removal from contaminated waters. Results showed that the degradation of PCA followed the pseudo-first-order kinetics in all conditions. PCA degradation efficiency increased with the increase of applied voltages in the range of 0–3.0 V. The optimum solution pH for PCA decay was 7.0. An initial PCA concentration higher than 30  μ M had no significant influence ( p  > 0.05) on the degradation efficiency of PCA. At an applied voltage of 2.0 V and an electrolysis time/hydraulic retention time of 2 h, the removal efficiency of PCA under flow-through mode was found to be 3.6 times that of flow-by mode, due to the better contact and reaction of contaminants with the oxidants generated in the vicinity of membrane surface. It also showed that OH arisen from anodic water oxidation reaction played a key role in PCA degradation. Benzoquinone, aniline, p -aminophenol, hydroquinone, malonic acid, succinic acid, oxamic acid, maleic acid, oxalic acid, α-ketoglutaric acid and formic acid were identified as the main PCA decay products, leading to a lower biological toxicity of the effluent. The system also demonstrated a favorable performance for contaminant elimination after a long-term operation. These results highlight the potential of this electrochemical microfiltration membrane system for efficient PCA degradation. Graphical abstract: Highlights: An electrochemical ceramic membrane with built-in electrodes was developed. Efficient p -chloroaniline (PCA) removal from contaminated waters was achieved. Removal rate of PCA under flow-through mode was about 3.6 times that of flow-by mode. OH generated at anode was found to play a key role in PCA degradation. Intermediate oxidation products were identified with a degradation pathway proposed.